Maternal Into‐The‐Face Behavior, Shared Attention, and Infant Distress During Face‐to‐Face Play at 12 Months: Bi‐directional Contingencies. (8th March 2018) - Galligan, Robert P.; Beebe, Beatrice; Milne, Dafne; Ewing, Julie; Lee, Sang Han; Buck, Karen A.
Abstract : We describe a new maternal intrusion behavior, moving a toy or hand "into‐the‐face" of the infant, and we investigate its bi‐directional associations with infant‐initiated shared attention, infant distress, and infant gaze, during mother–infant face‐to‐face play at 12 months. The play was videotaped split‐screen, with infants seated in a high chair. Videotapes were coded on a 1‐sec time base for mother and infant gaze (at partner, toy, both, or gaze away); infant distress; and maternal intrusion behavior, "into‐the‐face." We defined "infant‐initiated shared attention" as mother and infant looking in the same second at a toy that the infant‐initiated interest in. We documented that maternal into‐the‐face behavior decreased the likelihood of infant‐initiated shared attention, increased the likelihood of infant distress, and decreased the likelihood of infant gazing away. Reciprocally, infant distress and gazing away increased the likelihood of mother into‐the‐face. In moments when the dyad was engaged in infant‐initiated shared attention, mother into‐the‐face was less likely. This work documents bi‐directional contingencies in the regulation of maternal intrusion and infant behavior during face‐to‐face play at 12 months. We suggest that mother into‐the‐face behavior disturbs an aspect of the infant's experience of recognition.